«European philosophy has forgotten how to not really know»: refletion on the book by A. V. Smirnov «The logic of sense as a philosophy of mind» - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2022)
The concept of a multi-civilisational world, the philosophical foundations of which are set out in the new monograph of academician A. V. Smirnov «The logic of sense as a philosophy of mind» (2021). Historical experience and analysis of modern practice shows that a new multi-civilisational integrity will not work, as long as only the Western project is considered as the only possible perspective of modern civilisation, and its ideals and values are presented as a role model. At the same time, the implementation of the value orientations of the consumer society outside Europe generates new crises and contradictions, not fitting into the national and cultural characteristics of other countries. Therefore, the way out to the points of growth of a new civilisational integrity should be not found in the West at all, but should be explored in those cultures that have preserved the traditional soil under the influence of modernisation processes. The new civilisational world does not arise as a completed project; it grows out of the global dynamic chaos left over from the outgoing civilisation. The catalysts of civilisational changes on the way to a new integrity are values that carry changes in life meanings under the influence of social life. New risks and challenges faced by countries require timely and adequate changes. Recently, the world has faced global instability, adaptation to which has become a motive for the transition to a new model of civilisational development.